Electron-withdrawing substituted benzenesulfonamides against the predominant community-associated methicillin-resistant Staphylococcus aureus strain USA300 - Wanida Phetsang (2018)
A small focused chemical library constituted of sulfonamides was synthesized. These compounds were designed to lack the p-aminobenzene moiety typically found in sulfonamide antibiotics. Antimicrobial activities of these synthetic compounds were investigated against global predominant methicillin-resistant Staphylococcus aureus (MRSA) strain USA300 (SF8300) and control strains of Staphylococcus aureus (S. aureus) ATCC 25923 and ATCC 29213 using disk diffusion and microdilution assays. Based on susceptibility results, potent S. aureus and MRSA USA300 growth inhibitors such as N-[3,5- bis(trifluoromethyl)phenyl]-4-bromobenzenesulfonamide with minimum inhibitory concentration (MIC) as low as 5.6 μg/cm3along with other effective sulfonamides were discovered. Structure-activity correlations revealed that these desamino-benzenesulfonamides required electron-withdrawing substituents to be effective inhibitors of bacterial pathogen growth. In addition, their ability to inhibit growth of S. aureus strains was retained even when bacterial folate synthetic intermediate, p-aminobenzoic acid (PABA), was supplemented, whereas PABA supplementation completely diminished the antibacterial activity of the known sulfa drug tested, sulfamethoxazole. The sulfa-resistant MRSA strain COL also showed great susceptibility to these desamino-benzenesulfonamides. These results imply a unique mechanism of growth inhibition by these potent desamino-benzenesulfonamides, different from the well-known folate pathway target of sulfonamide antibiotics. © 2012 Springer-Verlag Wien.